2007
DOI: 10.1002/bit.21396
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for selecting and characterizing linker peptides for CBM9‐tagged fusion proteins expressed in Escherichia coli

Abstract: The influence of linker design on fusion protein production and performance was evaluated when a family 9 carbohydrate-binding module (CBM9) serves as the affinity tag for recombinant proteins expressed in Escherichia coli. Two bioinformatic strategies for linker design were applied: the first identifies naturally occurring linkers within the proteome of the host organism, the second involves screening peptidases and their known specificities using the bioinformatics software MEROPS to design an artificial lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 90 publications
(84 reference statements)
2
45
0
Order By: Relevance
“…N -terminal amino acid sequence analysis confirmed that proteolytic cleavage occurred in linker region (-ATTM↓STTT-, ↓ indicates cleavage site). This phenomenon might be related to the fact that inter-domain linkers are particularly susceptible to proteolysis [12]. The reason is that flexible regions can more easily adopt conformations compatible with the active site of endopeptidase [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…N -terminal amino acid sequence analysis confirmed that proteolytic cleavage occurred in linker region (-ATTM↓STTT-, ↓ indicates cleavage site). This phenomenon might be related to the fact that inter-domain linkers are particularly susceptible to proteolysis [12]. The reason is that flexible regions can more easily adopt conformations compatible with the active site of endopeptidase [12].…”
Section: Resultsmentioning
confidence: 99%
“…EcGAD possesses some superior enzymatic characteristics including a high affinity for substrate and high reaction rate compared to other GADs [1,4]. Some studies have focused on potential for industrial applications of EcGAD by improving its enzymatic properties and reaction conditions [6,9,12]. However, few studies have been performed on the immobilization of EcGAD for reuse [7]; in particular, there is no report of experiments using an affinity tag.…”
Section: Introductionmentioning
confidence: 99%
“…It is identified that different linkers affect soluble expression and stability of some fusion proteins (Kavoosi et al, 2007). In this study, two different linkers were independently incorporated between the maize protein and reporter, but their effect on improving protein expression was limited.…”
Section: Discussionmentioning
confidence: 98%
“…Flexible linkers are typically incorporated in cases where the fused domains require a certain degree of movement or interaction (Kim et al, 2000;Blazyk and Lippard, 2004;Jiang et al, 2005;Wang et al, 2007;Lu and Feng, 2008). Most commonly used flexible linker sequences primarily consist of Gly and Ser residues ("GS" linker) (Huston et al, 1988;Kavoosi et al, 2007;Hölsch and Weuster-Botz, 2010). (G 4 S 1 ) n is one such widely used sequence.…”
Section: Discussionmentioning
confidence: 99%